Ethno-Vlog Information Technology as an Interactive Learning Media Integrated with Local Knowledge - Saida Rahmed Binti Raside (Community Service Akseprin Journal, 2024)
Innovation and creation of learning media must continue to be carried out by a teacher so that the learning process remains relevant to the times. Vlog is one of the effective contemporary learning media. This can be done through integrating the knowledge that develops in the local community and presenting it into learning media to make it easier to relate the concept of learning to life. The integration of knowledge that develops in the local community into the learning presented through vlogs is known as ethno-vlog. Currently, teachers in the field are not familiar with learning media in the form of ethno-vlogs. Socialization of ethno-vlogs is carried out to provide understanding and increase insight for partners regarding learning media in the form of vlogs that are integrated with the knowledge or culture of the local community known as ethnoscience. Based on the results of the posttest above, it is known that the partner already knows what ethnoscience, vlogs, ethno-vlogs, and how to make ethno-vlogs. After participating in the socialization, participants have learned the concept of reconstructing ethnoscience into the form of ethno-vlogs and participants have learned how to relate ethno-vlogs in a learning material and feel that this ethno-vlog socialization activity as a learning medium is very beneficial for participants. This can be seen from the results of the posttest questionnaire given, which obtained a score of 100% each. Based on the results of the pretest and posttest of the ethno-vlog socialization activity as a contemporary learning media integrated with local knowledge, it can be stated that this activity is successful and can increase insight and ability to plan learning media